(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To determine the hospital-acquired infection (HAI) rate and associated factors at the Hospital for Rehabilitation - Professional Diseases in 2025. Methods: A retrospective cross-sectional study was conducted on 869 inpatient medical records from January 2025 to June 2025. HAIs were identified according to the Ministry of Health guideline (Decision No. 3916/QĐ-BYT). Frequencies and percentages were used for descriptive statistics. Chi-square and Fisher’s exact tests were applied for inferential analysis (p < 0.05). Results: The HAI rate was 4.14%. HAIs occurred predominantly in the respiratory tract, with Klebsiella spp. being the most common pathogen. Factors significantly associated with HAIs included the presence of chronic diseases, longer length of hospital stay, undergoing invasive procedures, and increased risk with a higher number of invasive procedures. Associated invasive procedures comprised peripheral venous catheterization, central venous catheterization, urinary catheterization, mechanical ventilation, tracheostomy, endotracheal intubation, and nasogastric tube placement. Conclusion: The HAI rate was relatively low; however, HAIs were mainly respiratory and were strongly associated with chronic comorbidities, prolonged hospitalization, and invasive interventions. Infection control efforts should prioritize high-risk patients and strengthen the care and monitoring of invasive devices.